The Influence of Capital Structure, Company Size, Investment Opportunity Set, Leverage, Liquidity and Profitability on Profit Quality in Banking Companies Listed on the BEI in 2019-2021 - Recka Lestari; Nina Andriany Nasution (Proceeding of The International Conference on Business and Economics, 2024)
The aim of this research is to determine the extent of the influence of Capital Structure (DAR), Company Size (Ln), Investment Opportunity Set (EPS), Leverage (DER), Liquidity (CR) and Profitability (ROA) on the Quality of Profits in banking companies. registered on the IDX in 2019-2021. The method used in this research is a quantitative descriptive method and multiple linear regression analysis, where the population in this research is 46 banks and uses a purposive sampling technique with the sample size being 34 banks registered on the BEI in 2019-2021. Based on the research results, it shows that partially only the variables Company Size (Ln) and Profitability (ROA) have a positive and significant effect on Earnings Quality, while Capital Structure (DAR), Investment Opportunity Set (EPS), Leverage (DER) and Liquidity (CR) has no effect on the Quality of Profits in Banking Companies listed on the IDX in 2019-2021. Simultaneously, the variables Capital Structure (DAR), Company Size (Ln), Investment Opportunity Set (EPS), Leverage (DER), Liquidity (CR) and Profitability (ROA) have a positive and significant effect on the Quality of Profits in Banking Companies listed on the IDX 2019 -2021.